The Effect of Tiktok on the Use of Standard Language in Grade 4 Elementary School Children - Devi Meilinda Nurviantika; Nanang Khoirul Umam (research, training and philanthropy institution Natural Aceh, 2023)
A study in grade 4 shows that using slang from the Tiktok application affects how children use familiar words. Identifying the influence of Tiktok on the use of standard terms in 4th-grade elementary school children is the aim of the researchers to conduct research. This research method collects data qualitatively to provide specific information about a particular problem. Qualitative and observational methods were used to collect this data, interviews and written tests. The subjects of this study were 26 grade 4 students of UPT SD Negeri 32 Gresik. This research on grade 4 students shows that half of the students use slang and mixed language. Also, common words are only used by half of the other students. With these results, teachers and parents can determine how much Tiktok impacts children's language styles